Metabolic activation of carcinogenic aristolochic acid, a risk factor for Balkan endemic nephropathy - Stiborová, Marie; Frei, Eva; Arlt, Volker M; Schmeiser, Heinz H (Mutation research, 2008)
Aristolochic acid (AA), a naturally occurring nephrotoxin and carcinogen, is associated with tumor development in patients suffering from Chinese herbs nephropathy (now termed aristolochic acid nephropathy, AAN) and may also be a cause for the development of a similar type of nephropathy, the Balkan endemic nephropathy (BEN). Major DNA adducts [7-(deoxyadenosin-N6-yl)-aristolactam and 7-(deoxyguanosin-N2-yl)aristolactam] formed from AA after reductive metabolic activation were found in renal tissues of patients with both diseases. Understanding which human enzymes are involved in AA activation and/or detoxication is important in the assessment of an individual's susceptibility to this plant carcinogen. This paper reviews major hepatic and renal enzymes responsible for AA-DNA adduct formation in humans. Phase I biotransformation enzymes play a crucial role in the metabolic activation of AA to species forming DNA adducts, while a role of phase II enzymes in this process is questionable. Most of the activation of AA in human hepatic microsomes is mediated by cytochrome P450 (CYP) 1A2 and, to a lower extent, by CYP1A1; NADPH:CYP reductase plays a minor role. In human renal microsomes NADPH:CYP reductase is more effective in AA activation. Prostaglandin H synthase (cyclooxygenase, COX) is another enzyme activating AA in human renal microsomes. Among the cytosolic reductases, NAD(P)H:quinone oxidoreductase (NQO1) is the most efficient in the activation of AA in human liver and kidney. Studies with purified enzymes confirmed the importance of CYPs, NADPH:CYP reductase, COX and NQO1 in the AA activation. The orientation of AA in the active sites of human CYP1A1, -1A2 and NQO1 was predicted from molecular modeling and explains the strong reductive potential of these enzymes for AA detected experimentally. We hypothesized that inter-individual variations in expressions and activities of enzymes activating AA may be one of the causes responsible for the different susceptibilities to this carcinogen reflected in the development of AA-induced nephropathies and associated urothelial cancer.
Keywords: Animals; Balkan Nephropathy; Molecular Structure; lidé; Carcinogens; Aristolochic Acids; chemické modely; Risk Factors; molekulární struktura; Cytochrome P-450 CYP1A2; karcinogeny; biotransformace; balkánská nefropatie; rizikové faktory; kyseliny aristolochové; Biotransformation; Models, Chemical; zvířata; cytochrom P-450 CYP1A2; Humans